The real life investing guide - Pollack, Kenan (McGraw-Hill, 1998)
Packed with important stuff you need to know, and spiced with real-life stories of "entry-level" investors, cool facts (like the fact that between your 18th and 30th birthdays, you will likely hold an average of 7.5 jobs), and references to rock and pop songs, this hip, "tell-it-like-it-is" guide focuses on the basics of investing, stocks and bonds, mutual funds, short term saving and long term investing. Emphasizing that a person is never too young to think about investing, it includes definitions of important terms and concepts such as return, liquidity, risk, dividend, yield, and the stock market indexes; information on how to research a company, purchase stock, and select a mutual fund; and detailed explanations of 401(k) plans and IRAs.